Prevalence and Mechanism of Atrazine Resistance in Waterhemp (Amaranthus tuberculatus) from Nebraska. Issue 5 (11th September 2018) - Vennapusa, Amaranatha Reddy; Faleco, Felipe; Vieira, Bruno; Samuelson, Spencer; Kruger, Greg R.; Werle, Rodrigo; Jugulam, Mithila
Abstract: Resistance to atrazine (a photosystem II [PSII] inhibitor) is prevalent in waterhemp [ Amaranthus tuberculatus (Moq.) J. D. Sauer] across the U.S. Midwest. Previous research suggests that target-site mutation or rapid metabolism of atrazine mediated by glutathione S -transferase (GST) conjugation confers resistance in A. tuberculatus from Illinois. The distribution and mechanism of resistance to atrazine in A. tuberculatus populations from Nebraska (NE) are unknown. In this research we (1) evaluated the response and frequency of resistance in NE A. tuberculatus to soil-applied PSII (metribuzin and atrazine) and protoporphyrinogen oxidase (sulfentrazone) inhibitors, as well as POST-applied atrazine; and (2) determined the mechanism of atrazine resistance in NE A. tuberculatus . The chloroplastic psbA gene, coding for a D1 protein (the target site of atrazine) was sequenced in 85 plants representing 27 populations of A. tuberculatus . Furthermore, 24 plants selected randomly from four atrazine-resistant (AR) populations were used to determine the metabolism of atrazine via GST conjugation. Results from the soil-applied herbicide evaluation suggest that metribuzin (0.56 kg ai ha −1 ) and sulfentrazone (0.28 kg ai ha −1 ) were effective on A. tuberculatus management. PRE and POST screenings against atrazine in the greenhouse indicate that atrazine (1.345 kg ai ha −1 ) was not effective on 39% and 73% of the A. tuberculatus populations evaluated (total of 109 and 85 populations, respectively), suggesting the prevalence of atrazine resistance in A. tuberculatus in NE. Sequence analysis of the psbA gene found no known point mutations conferring atrazine resistance. However, the AR plants conjugated atrazine via GST activity faster than the known atrazine-susceptible A. tuberculatus . Overall, the outcome of this study demonstrates the predominance of metabolism-based resistance to atrazine in A. tuberculatus from NE, which may predispose this species to evolve resistance to other herbicides. The use of integrated management strategies for A. tuberculatus is crucial for the control of this troublesome species.